Smart Governance in Public Financial Management: A Study of Government Resources Management System (GRMS) in the City of Surabaya - Sulikah Asmorowati; Erna Setijaningrum; Falih Suaedi; Yuniasih Fatmawati Dewi (Indonesian Association for Public Administration (IAPA), 2019)
This paper aims to examine the implementation of the Government Resource Management System (GRMS) in order to address problems in local government and local financial management from the Smart Governance point of view. It is based on a qualitative descriptive research involving interviews with various stakeholders, observation and analysis of relevant document. In line with its focus, this research uses smart city theory focusing on one of the dimensions that is relevant to this research problem, namely, smart governance. This research finds that the City Government of Surabaya has implemented the concept of Smart Governance in the management of regional finance through the GRMS system. The implementation of Smart Governance is evidence from five criteria, which include: 1) Participation in decision making: manifested in E-Planning process; 2) Public and social services: materialized in E-Procurement process; 3) Transparent Governance: manifested in e-Planning and e-Procurement processes in which in E-Planning the community is involved in the formulation of development planning through E-Musrenbang, and the auction process in E-Procurement; 4) Political strategies and perspectives: materialized in all GRMS processes because the whole system of GRMS is a strategy that integrates bureaucratic activities from upstream (the top or decision making level) to the downstream (to the community or citizen) so that it represents good local government and especially local financial management. By using GRMS, the overall local government and regional financial management process in the City of Surabaya can be done easily, effectively, efficiently, participatory and accountably.